Zhuiniu Water Buffalo Ritual of the Miao: Cultural Narrative Performed - Riccio, Thomas (Religions, 2022)
The zhuiniu 椎牛 ritual is one of the most elaborate of the Miao people of western Hunan, China. Zhuiniu means "kill the buffalo with a spear" and traces its origins to the worship of spirits and natural elements. Sponsored by a family to repay the spirits, the ritual was a village-wide event that culminated with the sacrifice of a water buffalo and a community celebration. The zhuiniu, estimated to be several thousand years old, is rapidly vanishing from cultural memory. In July and August of 2018, six master badai-spiritual specialists of the Miao—were gathered in La Yi 腊乙, a village in the Wuling Mountain by the cultural bureau of the Xiangxi Tujia-Miao Autonomous Prefecture of Hunan Province to reenact and document the ritual. Using performance ethnography as research methodology, the author employs on-site observations, interviews, field notes, audio, and video to document the reenactment and describe its significance in the words of its practitioners. This essay argues that the zhuiniu has no definitive expression but is an adaptative and interpretative cultural narrative adjusting to circumstances and practice. The ritual exists today as it had historically, in many and varied expressions and interpretations shaped by local need, geography, and subject to the vagaries to orally transmitted forms of practice. Although fragmentary in performance expression and interpretation, the zhuiniu ritual narrative serves as a mythologically-based script that organizes a series of dramatic events that invites community awareness and interaction. In so doing, this sacred ritual has sustained its importance in conveying, embodying, and encoding a spiritual, social, and cultural record of Miao cosmology, culture, and history. Performatively conveyed—using song, music, costumes, dance and movement, props, and set pieces—the zhuiniu has been efficiently and sensorially reimagined in order to reiterate and reaffirm cultural knowledge. With rural modernization, dissolution of cultural context and need, and the aging of its practitioners, the traditional role of the zhuiniu is now in question.